Land, politics, and memory in five Nija'ib' K'iche' títulos : "The title and proof of our ancestors" - Matsumoto, Mallory (University Press of Colorado, 2017)
"Five highland Maya títulos composed in the sixteenth century by the Nija'ib K'iche' of Guatemala. Each manuscript provides a copy of the original, a transcription of the sixteenth-century modified Latin script, a morphologic analysis, a line-by-line English translation preserving the original syntax, and English prose versions"--Provided by publisher.